Weekly intravenous bortezomib is effective and well tolerated in relapsed/refractory myeloma. (14th March 2013) - Moore, Sally; Atwal, Sangeeta; Sachchithanantham, Sajitha; Streetly, Matthew; Khan, Iftekhar; Percy, Laura; Narat, Santosh; D'Sa, Shirley; Rabin, Neil; Johnston, Rosalynd; Schey, Steve; Yong, Kwee
Abstract Objectives Bortezomib is an effective antimyeloma therapy, but clinical benefits can be limited by neurotoxicity. In newly diagnosed, older patients, modification of the biweekly dosing schedule to weekly regimens improves tolerability whilst maintaining efficacy. There is less information on the efficacy and tolerability of weekly bortezomib regimens in the relapsed/refractory setting. Here, we report our experience of weekly intravenous bortezomib in clinical practice in relapsed/refractory patients. Methods We analysed fifty‐two patients who received weekly bortezomib for relapsed/refractory MM. Results Thirty‐one per cent of patients received bortezomib beyond first relapse. Almost all (94%) also received steroids and 48% also received an alkylator. The median cumulative dose was 22.6 mg/m2, and median length of treatment was 164 d. Three patients reported grade 2 sensory neuropathy, and one reported grade 3 motor neuropathy. There were no grade 4 neurotoxicities. Eighty‐three per cent achieved a PR or greater, and the median PFS for the whole group was 13 months. One‐year PFS and OS were 53% (95% CI 39–66.6%) and 78% (95% CI 66.7–89.6%), respectively. Conclusions Weekly intravenous bortezomib when used in combination with steroids ± alkylator is effective in relapsed/refractory MM, producing outcomes comparable with biweekly regimens and with lower rates of peripheral neuropathy.